MODL-24. Focused ultrasound-mediated blood-brain barrier opening and panobinostat in a thalamic syngeneic murine DMG model is feasible and safe. (3rd June 2022) - Webster Carrion, Andrea; Wei, Hong-Jian; McQuillan, Nicholas; Tazhibi, Masih; Kokossis, Danae; Berg, Xander; Minns, Hanna; Zhang, Xu; Zhang, Zhiguo; Wang, Junqiang; Fernandez, Ester Calvo; Jan, Chia-Ing; et al.
Abstract: Diffuse Midline Glioma with H3K27M mutation (DMG) is an aggressive unresectable central nervous system tumor of the brainstem, midline thalamus, or spine. Prognosis is poor and systemic agents have been ineffective partially due to limited permeability of the blood brain barrier (BBB). Non-invasive low intensity focused ultrasound (FUS) can be used for BBB opening (BBBO). Our preclinical studies showed safety and feasibility of targeting and BBBO in the brainstem; however, to our knowledge, FUS-guided BBBO for thalamic DMG has yet to be reported. RNA-seq was performed on mouse syngeneic DMG cells 4423 (PDGFB+, H3.3K27M, p53−/−) and results recapitulated molecular programs seen in human tumors. 4423 cells were injected into the thalamus of male B6 (Cg)-Tyrc-2J/J mice at 1.6mm lateral and 1.8mm posterior to the bregma at a depth of 3.2mm. MRI at 14-21 days post injection confirmed thalamic tumor growth. Histological analysis with Hematoxylin and Eosin stain was consistent with thalamic DMG. Tumor implantation rate was 85% and median survival was 38 days post injection. To test safety and feasibility of BBBO for thalamic tumors, a 1.5 MHz FUS transducer was used with concurrent microbubble injection. BBBO assessed by contrast-enhanced MRI. FUS achieved BBBO targeting the thalamic tumor without increased morbidity or mortality and BBB closure was observed on day 3 post-sonication. Next we tested the tolerance of drug delivery with panobinostat post-FUS at a dose of 20mg/kg weekly. The results are preliminary at this time; however, animals tolerated the combination therapy without morbidity or mortality. Preclinical models are crucial to improve the development of new therapeutic strategies. Establishing this syngeneic thalamic DMG murine model provides the opportunity to test FUS as a non-invasive drug delivery technology for thalamic DMG compared to brainstem DMG, and to re-visit therapeutic agents previously considered ineffective due to limited penetration of the BBB.